Prospects for the sustainable development of russian business in the context of sanctions restrictions - O. V. Markova; N. N. Filimonova; T. A. Shpilkina; L. S. Artamonova (Путеводитель предпринимателя)
The presented research is devoted to relevant and fundamentally important aspects related to the prospects for sustainable development of Russian business in the context of sanctions restrictions. The research paper describes in sufficient detail the directions and factors of technological transformation of Russian business, analyzes the components of technological independence of small and medium–sized enterprises, and the main directions of government business support. The authors’ study highlights the problems of the development of some sectors of the economy, such as the IT industry,light industry, and the problems of of small and medium–sized businesses. The data on assistance in project activities by types of activities and branches of the manufacturing industry by the industrial development Fund for 2024 are presented, which contributes to the implementation of the import substitution program, scientific and technological business development through a system of scientific funds, competence centers, technology platforms and increasing the technological sovereignty of the country.